2015
DOI: 10.3144/expresspolymlett.2015.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon black on electrical and rheological properties of graphite nanoplatelets/poly(ethylene-butyl acrylate) composites

Abstract: Abstract. The effect of adding carbon black on the electrical and rheological properties of graphite nanoplatelets/poly(ethylene-butyl acrylate) copolymer composites produced via melt or solution mixing was studied. By adding a small amount of low-or high-structured carbon black to the nanocomposite, the electrical percolation threshold decreased and the final conductivity (at higher filler contents) increased. The effect on the percolation threshold was significantly stronger in case of the high-structured ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 32 publications
3
44
0
Order By: Relevance
“…It is known the that formation of a gel (or a percolating network) has a strong influence on the rheological properties of the system (Kim and Macosko 2009;Kotsilkova 2007;Oxfall et al 2015). The percolation threshold (u c ) can be estimated using different approaches.…”
Section: The Gel Concentrationmentioning
confidence: 99%
“…It is known the that formation of a gel (or a percolating network) has a strong influence on the rheological properties of the system (Kim and Macosko 2009;Kotsilkova 2007;Oxfall et al 2015). The percolation threshold (u c ) can be estimated using different approaches.…”
Section: The Gel Concentrationmentioning
confidence: 99%
“…The screen printing process has the ability to deposit thick layers of viscous slurries be they conductive metals or carbons, or indeed insulators and dielectrics, with high functional material loadings, and hence performance for the various applications. Carbon inks for screen printing are a commercially established technology, particularly in applications such as blood glucose sensors and while there is some literature on the influence of conductive carbon ratios in paints and composites [9,13,14], there is a lack of published literature into the interaction between graphite and carbon black and the effect of the ratios of these ingredients in inks. An abundance of composites studies uses the classical percolation theory to model electrical properties alongside experimental testing, but these only consider single types of carbon in any system [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Within a polymeric bonder, the complimentary interaction between these two types of carbon gives rise to a conductive matrix which is substantially more conductive than if these materials are used in isolation. The small carbon black particles readily disperse and form conducting bridges between the graphite rich areas of the composite matrix [9]. Carbon nanotubes have been studied extensively of late as alternative filler materials [10], but they are limited by their very high cost and tendency to agglomerate, making them difficult to process for volume applications [11].…”
Section: Introductionmentioning
confidence: 99%
“…By using the oscilloscope method within the frequency range 10 to 10 6 Hz at the temperature 492.1 K and pressure 11.31 MPa at the output of the single-screw extruder, dielectric properties of the composite consisting of linear low-density polyethylene, 20 wt.% of graphite and 10 wt.% of carbon black have been investigated. It has been shown that in the whole frequency range, dispersion of R and C on the frequency is observed.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Therefore, to expand their functionality, studies are performed using different types of polymers and fillers [1][2][3][4][5][6][7][8]. In recent years for such studies, the use of nanoparticles is typical [9][10].…”
Section: Introductionmentioning
confidence: 99%